2015
DOI: 10.1371/journal.pone.0138317
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of CX3CR1 Deficiency in Diet-Induced Obese Mice

Abstract: The fractalkine (CX3CL1-CX3CR1) chemokine system is associated with obesity-related inflammation and type 2 diabetes, but data on effects of Cx3cr1 deficiency on metabolic pathways is contradictory. We examined male C57BL/6 Cx3cr1-/- mice on chow and high-fat diet to determine the metabolic effects of Cx3cr1 deficiency. We found no difference in body weight and fat content or feeding and energy expenditure between Cx3cr1-/- and WT mice. Cx3cr1-/- mice had reduced glucose intolerance assessed by intraperitoneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
1
22
2
1
Order By: Relevance
“…Interestingly, one of the strongest correlations we observed were between fractalkine receptor Cx3cr1 and fat mass response (p = 9.62E–10). Fractalkine (Cx3cl1) is a chemokine, that was recently implicated in diet induced obesity, insulin regulation and promotion of hypothalamic inflammatory response to fatty acids ( Shah et al, 2015 ). However, different models of Cx3cr1 knockout mice resulted in variable results on diet induced obesity.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, one of the strongest correlations we observed were between fractalkine receptor Cx3cr1 and fat mass response (p = 9.62E–10). Fractalkine (Cx3cl1) is a chemokine, that was recently implicated in diet induced obesity, insulin regulation and promotion of hypothalamic inflammatory response to fatty acids ( Shah et al, 2015 ). However, different models of Cx3cr1 knockout mice resulted in variable results on diet induced obesity.…”
Section: Resultsmentioning
confidence: 99%
“…A study indicated that O 2 consumption peaks in C57BL/6 mice around 7 pm (Shah et al. ), so the time period we selected at night (8–11 pm ) may also contribute to the observation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our hypothesis, these pathways, which are interrelated, have been described to play important roles in weight gain and in the appearance of T2D‐associated obesity. Explicitly, CDKN1A and MYC have been related to obesity , while CX3CL1, ECE1, STAT3, TNF, GLUL, and IL1β have been reported to be related to both obesity and T2D‐associated inflammation . Other studies have shown that HIF1A, KDR, VEGFA, GPI, and NOS3 were mainly associated with IR and obesity‐associated angiogenesis and that ZNF274 was related to obesity and IR .…”
Section: Discussionmentioning
confidence: 99%